2020
DOI: 10.3390/cancers12010208
|View full text |Cite
|
Sign up to set email alerts
|

The EGFR-TMEM167A-p53 Axis Defines the Aggressiveness of Gliomas

Abstract: Despite the high frequency of EGFR and TP53 genetic alterations in gliomas, little is known about their crosstalk during tumor progression. Here, we described a mutually exclusive distribution between mutations in these two genes. We found that wild-type p53 gliomas are more aggressive than their mutant counterparts, probably because the former accumulate amplifications and/or mutations in EGFR and show a stronger activation of this receptor. In addition, we identified a series of genes associated with vesicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In CNV analysis, we found focal amplification peaks for oncogenes in the high PDIA5 group and focal deletion peaks for tumor suppressor genes. Several common somatic mutations in GBM including TP53, TTN, PTEN, and EGFR ( 52 ), were also present in the high PDIA5 group. These results suggest that high PDIA5 expression plays an important role in glioma infiltration.…”
Section: Discussionmentioning
confidence: 95%
“…In CNV analysis, we found focal amplification peaks for oncogenes in the high PDIA5 group and focal deletion peaks for tumor suppressor genes. Several common somatic mutations in GBM including TP53, TTN, PTEN, and EGFR ( 52 ), were also present in the high PDIA5 group. These results suggest that high PDIA5 expression plays an important role in glioma infiltration.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have suggested that tumors with immune-excluded phenotype also show infiltration of immune cells because the latter remain in the matrix around the tumor cell “nests” rather than penetrating the parenchyma of tumor cells ( 50 , 51 ). Moreover, we revealed a significant correlation between the subtypes and TMB, including several common somatic mutations (TP53, PTEN, and EGFR) in gliomas ( 52 ). mt-rRNA modification played an important part in formation of the “immune landscape” of the TME, which suggests that mt-rRNA modification may affect the therapeutic efficacy of ICBs.…”
Section: Discussionmentioning
confidence: 86%
“…Little is known about TMEM167A, but it has prognostic significance in lung cancer and glioma [ 57 , 58 ]. TMEM167A regulates vesicular trafficking, TNF and EGF signaling, and p53 transcription [ 29 ]. The compound silibinin has been shown to inhibit the TMEM family of receptors [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%